ABCDE cognitive aid tool in patient assessment - development and validation in a multicenter pilot simulation study - Peran, David; Kodet, Jiri; Pekara, Jaroslav; Mala, Lucie; Truhlar, Anatolij; Cmorej, Patrik Christian; Lauridsen, Kasper Glerup; Sari, Ferenc; Sykora, Roman (BMC emergency medicine, 2020)
BACKGROUND: The so called ABCDE approach (Airway-Breathing-Circulation-Disability-Exposure) is a golden standard of patient assessment. The efficacy of using cognitive aids (CA) in resuscitation and peri-arrest situations remains an important knowledge gap. This work aims to develop an ABCDE CA tool (CAT) and study its potential benefits in patient condition assessment. METHODS: The development of the ABCDE CAT was done by 3 rounds of modified Delphi method performed by the members of the Advanced Life Support Science and Education Committee of the European Resuscitation Council. A pilot multicentre study on 48 paramedic students performing patient assessment in pre-post cohorts (without and with the ABCDA CAT) was made in order to validate and evaluate the impact of the tool in simulated clinical scenarios. The cumulative number and proper order of steps in clinical assessment in simulated scenarios were recorded and the time of the assessment was measured. RESULTS: The Delphi method resulted in the ABCDE CAT. The use of ABCDE CAT was associated with more performed assessment steps (804: 868; OR = 1.17, 95% CI: 1.02 to 1.35, p = 0.023) which were significantly more frequently performed in proper order (220: 338; OR = 1.68, 95% CI: 1.40 to 2.02, p < 0.0001). The use of ABCDE CAT did not prolong the time of patient assessment. CONCLUSION: The cognitive aid for ABCDE assessment was developed. The use of this cognitive aid for ABCDE helps paramedics to perform more procedures, more frequently in the right order and did not prolong the patient assessment in advanced life support and peri-arrest care.
Keywords: směrnice jako téma; Checklist; Female; pomocný zdravotnický personál; Delphi Technique; Patient Simulation; kontrolní seznam; mladý dospělý; ženské pohlaví; lidé; ABCDE approach; Life Support Care; Pilot Projects; Peri-arrest; osoby simulující pacienta ve výuce; pilotní projekty; Allied Health Personnel; delfská metoda; Advanced life support; Curriculum; Triage; kognice; Guidelines as Topic; Male; Czech Republic; Young Adult; Cognition; Patient assessment; Česká republika; kurikulum; třídění pacientů; mužské pohlaví; resuscitační péče; Humans